Keterikatan Kerja sebagai prediktor Eudaimonic Well-Being Pada Pegawai - kadek putri lestari wardani; Ni Putu Lilik Agestin (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2026)
The rapid development of Society 5.0 places human resources as the central driver of organizational success, making employee well-being an important aspect to consider. This study aims to examine the relationship between work engagement and eudaimonic well-being among employees. The research used a quantitative survey design involving 135 permanent employees from a company in the airport service sector. Data were collected using self-report questionnaires measuring work engagement and eudaimonic well-being. The instruments used were adapted from established scales, and data were analyzed using correlation analysis. The results showed that work engagement has a positive relationship with eudaimonic well-being. Employees who demonstrate higher levels of vigor, dedication, and absorption in their work tend to experience greater meaning in life, personal growth, and eudaimonic well-being. These findings highlight the importance of fostering work engagement as a strategy to enhance wellbeing in the workplace Keywords: eudaimonic well-being; employees; work engagement; workplace